"Bright Band Sign" A Grayscale Ultrasound Finding in Hepatic Infarction. (21st January 2019) - Whang, Gilbert; Chopra, Shefali; Tchelepi, Hisham
Abstract : Hepatic infarction is infrequent due to the dual blood supply of the liver and the compensatory relationship between the hepatic artery and portal vein. Most cases occur in liver transplants due to vascular complications. Grayscale sonography combined with color and spectral wave Doppler can assess for vessel patency and parenchymal abnormalities. Liver infarctions appear as hypoechoic nonvascular regions on conventional and Doppler sonography. Here, we describe a grayscale ultrasound feature within liver infarctions in 2 liver transplants and in 1 native liver due to iatrogenic complication. This feature is similar to those described recently in the literature within splenic infarcts.